A Room‐Temperature Verwey‐type Transition in Iron Oxide, Fe5O6. (30th January 2020) - Ovsyannikov, Sergey V.; Bykov, Maxim; Medvedev, Sergey A.; Naumov, Pavel G.; Jesche, Anton; Tsirlin, Alexander A.; Bykova, Elena; Chuvashova, Irina; Karkin, Alexander E.; Dyadkin, Vadim; Chernyshov, Dmitry; Dubrovinsky, Leonid S.
Abstract: Functional oxides whose physicochemical properties may be reversibly changed at standard conditions are potential candidates for the use in next‐generation nanoelectronic devices. To date, vanadium dioxide (VO2 ) is the only known simple transition‐metal oxide that demonstrates a near‐room‐temperature metal–insulator transition that may be used in such appliances. In this work, we synthesized and investigated the crystals of a novel mixed‐valent iron oxide with an unconventional Fe5 O6 stoichiometry. Near 275 K, Fe5 O6 undergoes a Verwey‐type charge‐ordering transition that is concurrent with a dimerization in the iron chains and a following formation of new Fe−Fe chemical bonds. This unique feature highlights Fe5 O6 as a promising candidate for the use in innovative applications. We established that the minimal Fe−Fe distance in the octahedral chains is a key parameter that determines the type and temperature of charge ordering. This model provides new insights into charge‐ordering phenomena in transition‐metal oxides in general. Abstract : Bringt Ordnung in die Ladung : Kristalle von neuartigem gemischt‐valentem Eisenoxid mit einer ungewöhnlichen Fe5 O6 ‐Stöchiometrie wurden hergestellt und untersucht. Nahe 275 K durchläuft Fe5 O6 einen Ladungsordnungsübergang des Verwey‐Typs, der einhergeht mit einer ausgeprägten Dimerisierung und der Bildung neuer Fe‐Fe‐Bindungen. Dieses einzigartige Merkmal zeigt, dass Fe5 O6 vielversprechend für die Nutzung in innovativen Anwendungen ist.